13 Redox regulation of Jagged1 modulates cell cycle, adhesion and ECM pathways in endothelial cells. (22nd March 2023) - Cottrill, Shawn; Murdoch, Colin; Phair, Iain; Howden, Andy
Abstract : Jagged1 (Jag1) has essential roles in angiogenesis and development. Altered function of this transmembrane protein results in congenital birth defects and cancer progression. Redox signalling regulates cardiovascular physiology through Endothelial cells (EC). Proteins sense redox signals through cysteine thiols. Free radicals react with redox sensitive cysteines and form oxidative post translational modifications (Ox-PTM) which alters protein function. The effect of redox signalling on Jag1 has not yet been investigated. However, we have identified Jag1 as a redox target in ECs. Additionally, this signalling regulates expression of proteins involved in adhesion, the cell cycle, and the extracellular matrix (ECM). An Iodo-TMT redox proteomics screen was performed to identify Ox-PTMs in ECs involved in vascular signalling mechanisms. A group of proteins involved in angiogenesis was identified including Jag1, one of the canonical Notch ligands. The patterning of blood vessel sprouts during angiogenesis is regulated by Notch-Jag interactions. Quantitative proteomics was performed to determine changes in protein expression between WT and a redox-insensitive variant of Jag1. This 'redox dead' (RD) variant was generated through cysteine to serine substitutions. Human umbilical vein ECs (HUVEC) transiently expressing these Jag1 variants were treated with H2 O2 or VEGF. Jag1RD downregulated proteins related to adhesion and the ECM while upregulating cell cycle proteins. Using the histone ruler method, protein content per cell was estimated. This showed lower protein in cells expressing Jag1RD compared to Jag1WT, correlating with an increased cell cycle rate. Results show that Jag1 redox modifications alter important EC processes which may be Notch-independent.